Performance analysis of dropped calls and blocked calls in realistic mobile system in sub urban areas / Ahmad Tarmizi Ahmad Taufek - Ahmad Taufek, Ahmad Tarmizi (2007)
The goal of this project is to analyze the performance of dropped calls and blocked calls in GSM network systems focusing in sub urban areas. The dropped calls is refers to the situation when mobile had established call having terminated unexpectedly. It occurred when this event generated if the call is abnormally ended after the event call established. For the blocked calls it is defined as the congest traffic in order to access the network in certain peak time with too many users are using on that time. The data was collected by using Test Mobile System (TEMS) tools and Key Performance Indicator (KPI) database system. The results obtained can be used as reference for troubleshooting.